2013
DOI: 10.1080/21551197.2012.722888
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Food Insecurity Is Associated With Higher Levels of Cost-Related Medication Nonadherence in Low-Income Older Adults

Abstract: The purpose of this study was to examine relationships between changes in food insecurity (FI) and cost-related medication nonadherence (CRN) among Older Americans Act Nutrition Program participants and wait-listed individuals in Georgia. This study used data collected from 3 waves of self-administered mail surveys conducted 4 months apart in 2008 and 2009 (n = 664, mean age 74.6 ± 8.9 years, 71.5% female, 31.0% African American). FI was assessed by using a validated 6-item U.S. Household Food Security Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 21 publications
(33 reference statements)
2
38
0
Order By: Relevance
“…This study, which was restricted to adults with chronic diseases, found that people living in food-insecure households were more likely to report CRMU. Similar findings have been demonstrated from smaller studies in different parts of the country among the non-elderly (25)(26)(27)(28)(29) and among low-income older adults (30)(31)(32).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This study, which was restricted to adults with chronic diseases, found that people living in food-insecure households were more likely to report CRMU. Similar findings have been demonstrated from smaller studies in different parts of the country among the non-elderly (25)(26)(27)(28)(29) and among low-income older adults (30)(31)(32).…”
supporting
confidence: 83%
“…We use the nationally representative National Health Interview Survey, as did Berkowitz and colleagues, but focus on older adults, and we do not limit the analysis to those with chronic diseases (18). Bengle and colleagues (30) and Sattler and colleagues (31,32) also focus on older adults, but their sample is limited to participants of the Older Americans Act Nutrition Program (receiving delivered meals or congregate meals) or those on a waitlist for services in Georgia. The association between FI and CRMU among older adults who sought out or were referred to nutrition assistance programs may differ from the general population of older adults.…”
mentioning
confidence: 99%
“…Studies have been conducted to analyse: the relationship between physical and cognitive functioning and food intake variety and diversity (Lee & Frongillo ,b, Clausen et al . ); cost‐related medication non‐adherence (Sattler & Lee ); and diabetes status (Sharkey ).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to separate whether polypharmacy worsens malnutrition or whether these 2 occurrences coexist in the vulnerable population of the elderly, with or without medical morbidity, and social deprivation factors like food insecurity. 23,44 It should be noted, however, that medications have common side effects that may be easily overlooked, such as dyspepsia or gastrointestinal intolerance. Furthermore, certain commonly prescribed medications have side effects affecting nutritional status such as anorexia, early satiety, reduced ability to eat, dysphagia, constipation, and diarrhea.…”
Section: Promoting Dietary Intake and Setting Reasonable Goalsmentioning
confidence: 98%
“…Poor economic conditions lead to malnutrition because of food insecurity. 23 If an elderly person needs assistance with activities of daily living and help is not available, the individual will also be predisposed to malnutrition. Bereavement in the elderly may be a pathologic state because some elderly individuals may not recover fast enough after loss of a loved one without accruing long-term decline in their level of functioning.…”
Section: Risk Factors For Malnutrition In the Elderlymentioning
confidence: 99%